The parental care-seeking behavior of children with osteogenesis imperfecta based on the Anderson’s model: a qualitative study - Lin Mo; Fan-yan Du (BMC Nursing)
Abstract Objective This study aims to analyze the medical-seeking behavior of Osteogenesis Imperfecta(OI) children in Southwest China, summarize and analyze the issues in their medical process, and propose corresponding improvement strategies. Methods A phenomenological study involving semi-structured interviews with 20 OI caregivers at a tertiary centre for children from March to August 2021 was analyzed thematically, following Anderson’s model. Results We identified eight themes in the data: 1)Regional disparities of OI management, 2)Big economic burden, 3)High-risk population, 4)Lack of health education, 5)Multiple treatments,6)Strict treatment indications,7)Disappointing therapeutic outcomes,8)Effective or ineffective treatment results. Discussion The current rare disease insurance policies do not cater to the needs of the OI community. The treatment fees are excessively high, surpassing the financial limits of patient families. Caregivers, lacking sufficient knowledge of the disease, find it difficult to manage the condition effectively. There is a pressing need for the state to revise relevant policies, and for tertiary hospitals, grassroots medical institutions, and specialized medical personnel to each shoulder their responsibilities in the treatment and management of rare diseases. Conclusions OI patients face many challenges in seeking care behavior. Improving access to medical resources, promoting collaboration between specialists and general practitioners, reforming insurance for rare diseases, leveraging social resources, and educating families can boost OI diagnosis rates and enhance family disease management.